-13x+-6=59

Simple and best practice solution for -13x+-6=59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13x+-6=59 equation:


Simplifying
-13x + -6 = 59

Reorder the terms:
-6 + -13x = 59

Solving
-6 + -13x = 59

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -13x = 59 + 6

Combine like terms: -6 + 6 = 0
0 + -13x = 59 + 6
-13x = 59 + 6

Combine like terms: 59 + 6 = 65
-13x = 65

Divide each side by '-13'.
x = -5

Simplifying
x = -5

See similar equations:

| 6-(3-2X)=8+X | | -9.8-(-1.2)= | | 1.23-(-3.45)= | | 9(-4n-12)= | | 7x+.1+10x-.2=5 | | 3x+y=6forx | | x^4+x^3=4x^2+4x | | -5(-5w+1)= | | 10-6w=-10 | | 3x-(2x+6)=2x-24 | | 8h=40 | | 2(-7v-8)=-86 | | 8B=-5+8B | | 2j=56 | | 25x+-45=180 | | 2(-2c-9)= | | 43=k-14 | | 3+2=-7 | | 7(5k+2)= | | 525+0.21d=585+0.13d | | 8x+3+4x=90 | | X^2-8x+12=24 | | -8(4m-9)= | | y^2=20-x^2 | | 8g-6g=8 | | 2x+1-x=-12 | | -w+173=3 | | 246=193-v | | 233-u=127 | | 49x^8+42x^4+9=f(x) | | 36-3w=w | | 7(6k-4)+3k=-388 |

Equations solver categories